Can repetitive transcranial magnetic stimulation be considered effective treatment option for negative symptoms of schizophrenia? - Prikryl, Radovan; Kucerova, Hana Prikrylova (The journal of ECT, 2013)
OBJECTIVE: Despite the development of second-generation antipsychotic drugs, treatment-resistant symptoms still represent a serious problem in schizophrenia. The aim of the present article was to review studies with repetitive transcranial magnetic stimulation for negative symptoms of schizophrenia and draw conclusions for clinical decision making. METHOD: Literature for this review was identified by searching MEDLINE and ISI Web of Science up to the year 2011. RESULTS: Five open studies, 13 sham-controlled studies, and 2 meta-analysis and 2 review articles were included in the present paper. The effect size of the high frequency repetitive transcranial magnetic stimulation (rTMS) over the left prefrontal cortex in the treatment of negative symptoms of schizophrenia is thought to be mild to moderate (Cohen d = 0.43-0.68). CONCLUSION: Despite the promising results of some rTMS studies, the potential of rTMS for the treatment of negative symptoms is currently relatively unclear. Large clinical studies are therefore needed, especially large multicentric studies such as depression rTMS studies.
Keywords: Age Factors; Transcranial Magnetic Stimulation; mozková kůra; Dose-Response Relationship, Radiation; transkraniální magnetická stimulace; výsledek terapie; Patient Compliance; Humans; Clinical Trials as Topic; lidé; schizofrenie; schizofrenie (psychologie); Research Design; vztah dávky záření a odpovědi; adherence pacienta; Randomized Controlled Trials as Topic; klinické zkoušky jako téma; Schizophrenia; Double-Blind Method; randomizované kontrolované studie jako téma; Treatment Outcome; Cerebral Cortex; věkové faktory; dvojitá slepá metoda; Schizophrenic Psychology; výzkumný projekt